2013
DOI: 10.2528/pier12111502
|View full text |Cite
|
Sign up to set email alerts
|

Two Dimension Digital Beamforming Preprocessing in Multibeam Scansar

Abstract: Abstract-The novel multibeam ScanSAR takes advantage of the displaced phase center multiple azimuth beam (DPCMAB) imaging scheme and intra-pulse beam steering in elevation in ScanSAR to achieve the high-resolution ultra-wide-swath imaging capacity. This letter proposes an innovative two-dimensional (2D) digital beamforming (DBF) space-time preprocessing approach for multibeam ScanSAR. According to echo proprieties of such imaging scheme, both azimuth ambiguity and range ambiguity problems should be resolve bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Due to its compressed sampling ability, compressed sensing has found many attractions in radar remote sensing and branched out to many new fronts. R. Baraniuk et al proposed the radar imaging system based on CS for the first time and a high resolution imaging method is presented in for SAR sparse targets reconstruction based on CS theory [7][8][9][10][11][12][13][14][15]. In the above researches, it has been shown that a successful recovery of a compressible signal depends on the presence of sparse dictionary and these works have made a great contribution to the future research of radar signal processing.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its compressed sampling ability, compressed sensing has found many attractions in radar remote sensing and branched out to many new fronts. R. Baraniuk et al proposed the radar imaging system based on CS for the first time and a high resolution imaging method is presented in for SAR sparse targets reconstruction based on CS theory [7][8][9][10][11][12][13][14][15]. In the above researches, it has been shown that a successful recovery of a compressible signal depends on the presence of sparse dictionary and these works have made a great contribution to the future research of radar signal processing.…”
Section: Introductionmentioning
confidence: 99%
“…Spotlight obtains very fine resolution while it cannot observe the earth continuously in azimuth [2]. Other techniques including wide swath imaging via elevation and azimuth multiple beams [3,4] or azimuth digital beam forming [5][6][7] and high resolution wide swath (HRWS) imaging via multidimensional waveform encoding are proposed [8], while they cause the system complexity ascension, reliability reduction, or signal processing difficulty increasing.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain wide swath coverage and high resolution, one can utilize two-dimensional array to transmit and receive SAR signals and then resolve the range and azimuth ambiguity [13]. However, this method makes range point target downlooking angle as range steer vector in approximate treatment and does not consider the changing of the downlooking angle with the azimuth time.…”
Section: Introductionmentioning
confidence: 99%